2021
DOI: 10.1556/2054.2020.00137
|View full text |Cite
|
Sign up to set email alerts
|

Culture and psychedelic psychotherapy: Ethnic and racial themes from three Black women therapists

Abstract: Psychedelic medicine is an emerging field of research and practice that examines the psychotherapeutic effects of substances classified as hallucinogens on the human mind, body, and spirit. Current research explores the safety and efficacy of these substances for mental health disorders including anxiety, depression, and posttraumatic stress disorder (PTSD). Although current studies explore psychotherapeutic effects from a biomedical perspective, gaps in awareness around cultural issues in the therapeutic proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 51 publications
(43 reference statements)
1
42
0
Order By: Relevance
“…These concerns are not unfounded. Psychedelic-assisted therapy can be unsafe when it is led by an inexperienced provider or a therapist who does not understand the nuances of racism ( 14 ). This paper aims to shine a light on the situation of those in the BIPOC community who could benefit from psychedelic treatments and provide a road map for greater access to psychedelic-assisted treatment.…”
Section: Positionality Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns are not unfounded. Psychedelic-assisted therapy can be unsafe when it is led by an inexperienced provider or a therapist who does not understand the nuances of racism ( 14 ). This paper aims to shine a light on the situation of those in the BIPOC community who could benefit from psychedelic treatments and provide a road map for greater access to psychedelic-assisted treatment.…”
Section: Positionality Statementmentioning
confidence: 99%
“…It is important to note that psychedelic substances are not designed to be a panacea of racial healing or trauma healing. Without a trained specialist in the treatment of trauma, and specifically race-based trauma, these experiences can leave the patient vulnerable to their emotions and further add to their trauma (e.g., ( 14 )). In fact, true healing relies on societal change within multiple institutions and community support along with corrective interpersonal experiences of safety.…”
Section: Introduction To Psychedelic Therapiesmentioning
confidence: 99%
“…Issues of personality and identity have received some attention in research on set and setting. Early psychedelic research proposed that personality structures play a large role in determining therapeutic outcomes ( Sandison, 1956 ; Eisner and Cohen, 1958 ), while more recent writing focused on identity ( Saldanha, 2007 ; Cavnar, 2014 ; Devenot, 2016 ; Neitzke-Spruill, 2020 ; Williams et al, 2020 ).…”
Section: Set: Preparation Expectation and Intentionmentioning
confidence: 99%
“…A study by Hook et al (2016) found that some of the most common microaggressions committed by therapists included a denial or lack of awareness of stereotypes and bias, and avoidance of discussing cultural issues. This can cause problems in psychedelic-assisted therapy if cultural or racial materials arise during sessions and therapists are not prepared to address it in a skillful manner (Williams et al, 2020b). When treating clients who have experienced discrimination, it is important that they approach these disclosures with openness, curiosity, and maintain cultural humility.…”
Section: Recommendations To Clinicians and Studentsmentioning
confidence: 99%